STUDENTS’ PERCEPTION ON THE USE OF SOCIAL MEDIA IN LEARNING ENGLISH AT TADULAKO UNIVERSITY - Muh. Arasy Hairul; Nurhayati Nurhayati (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2023)
ABSTRACTThe purpose of this study was to explore students’ perceptions on the use of social media in learning English. The research design used in this study was qualitative research based on a case study approach, and the data were collected through interview transcripts and documents. The participants of this study were five students of the English education department of Tadulako University selected purposively. The results of descriptive analysis showed that most of the students had positive perceptions on the use of social media in learning English. Social media was believed to be helpful in improving students' English language skills. They stated that social media provides them with English content sources to practice their English skills, particularly listening, speaking, vocabulary, and pronunciation. Moreover, social media offers a variety of English contents, allowing students to access and choose contents that they like anytime and anywhere. Youtube and Instagram are the most widely used social media platforms for learning English in receptive skills including listening and reading skills.ABSTRAKTujuan dari penelitian ini adalah untuk mengeksplorasi persepsi siswa tentang penggunaan media sosial dalam pembelajaran bahasa Inggris. Desain penelitian yang digunakan dalam penelitian ini adalah penelitian kualitatif dengan pendekatan studi kasus. Data dikumpulkan melalui transkrip wawancara dan dokumen. Partisipan dalam penelitian ini adalah 5 orang mahasiswa jurusan Pendidikan Bahasa Inggris Universitas Tadulako. Hasil analisis deskriptif menunjukkan bahwa sebagian besar siswa memiliki persepsi positif tentang penggunaan media sosial dalam pembelajaran bahasa Inggris. Media sosial sangat membantu dalam meningkatkan kemampuan berbahasa Inggris siswa. Mereka menyatakan bahwa media sosial memberi mereka sumber konten bahasa Inggris untuk melatih keterampilan bahasa Inggris mereka, terutama mendengarkan, berbicara, memperluas kosa kata mereka, dan meningkatkan pengetahuan pengucapan mereka. Media sosial menawarkan konten bahasa Inggris yang beragam, memungkinkan siswa untuk mengakses konten bahasa Inggris yang mereka sukai kapan saja dan di mana saja. Youtube dan Instagram adalah platform media sosial yang paling banyak digunakan untuk belajar bahasa Inggris dalam keterampilan reseptif, keterampilan mendengarkan, dan keterampilan membaca.How to Cite: Hairul, M.A., Nurhayati. (2023). Students’ Perception on the Use of Social Media in Learning English At Tadulako University. IJEE (Indonesian Journal of English Education), 10(1), 160-181. doi:10.15408/ijee.v10i1.31853.